Olmsted and America's urban parks [videorecording (DVD)] - Messner, Rebecca; DeGolian, George; Washington, Kerry, 1977-; Kline, Kevin (PBS Distribution, 2012)
Olmsted and America's Urban Parks, examines the visionary urban planner and landscape architect's impact on the development of America's first great city parks. Told in large part through Olmsted's own words, this film weaves together his poignant personal story and pioneering vision with contemporary footage of the lasting masterpieces he left behind.